Determination of the total phenolic content of tomato plant treated with exteacts of banana peels(Musa sp.)and horsetail plant(Equsietum arvense)and their effects in stimulating plant resistance against the fungus(Botrytis cinerea). (Latakia University Journal -Biological Sciences Series, 2024)
The results showed that the methanolic extract of banana peels, when applied sprayed to the leaves at concentrations (1-2-5%), gave successive pathogenicity to the isolate of the fungus B. cinerea (91.66 - 41.66 - 33.33%) compared to the control (91.66%), When used as irrigation in the soil at concentrations (1-2 - 5%), it gave respectively a pathogenicity intensity for the fungus isolate (66.66 -50 – 25)%   When applying the methanol extract of the horsetail plant L. E. arvense sprayed on the leaves at concentrations (1-2-5%), it gave successive pathogenicity to the isolate of the fungus B. cinerea (66.66 - 33.33 - 16.66%) compared to the control (91.66%), when used as irrigation in the soil at concentrations (1 - 2 - 5%), it gave, respectively, a pathogenicity intensity for the fungus isolate (58.33 - 41.66 - 8.33) %).   The results showed an increase in the total phenolic content of tomato plants under the influence of horsetail extract, as it reached in the spraying treatment on the leaves at concentrations (1-2-5%), respectively, mg/L (60-90-115), and in the soil irrigation treatment it reached over Respectively, mg/L (85-125-153), and under the influence of banana peel extract, the total phenolic content of tomato plants in the foliar spraying treatment reached (1-2-5%), respectively, mg/L (54-63-70). In the soil irrigation treatment, it reached (56-66-80) mg/L respectively, compared to the control (60 mg/L (without treatment and with infection).